Apartheid climático en el desarrollo: reflexiones desde la (in)justicia socioambiental de las poblaciones negras de Nigeria - Chávez Aguilar, Maria Fernanda (2023)
The idea of development articulated by the project of capitalist-colonial-heteropatriarchal modernity has necessarily implied violence, dispossession, subjugation and, in short, underdevelopment of the human and non-human lives that shape Nigeria. In the face of climate change, accelerated by activities based on human and non-human relations of exploitation and domination, which threatens the idea of development, various experts have focused on adaptation and mitigation actions, seeking to reduce the levels of greenhouse gases responsible for climate change and thereby slow the pace and severity of climate-related impacts. However, these responses continue to reproduce systems of discrimination, segregation and displacement by attempting to adapt to the climate crisis while safeguarding the dominant economic and socio-political structures that caused it. This is what is causing climate apartheid. The aim of this text is to analyze the implications of the development project, from the differentiated impacts of anthropogenic climate change, particularly for populations in Nigeria, understanding the complex articulations of racism in the context of socio-environmental crisis itself, especially taking up the supposed solutions given to the latter.